A self-healing architecture for Web service-based applications - Pegoraro, Renê [UNESP] (2008)
Web service-based application is an architectural style, where a collection of Web services communicates to each other to execute processes. With the popularity increase of developing Web service-based application and once Web services may change, in terms of functional and non-functional Quality of Service (QoS), we need mechanisms to monitor, diagnose, and repair Web services into a Web Application. This work presents a description of self-healing architecture that deals with these mechanisms. Other contributions of this paper are using the proxy server to measure Web service QoS values and to employ some strategies to recovery the effects from misbehaved Web services. © 2008 IEEE.